A 20-year follow-up evaluation of total hip arthroplasty in patients younger than 50 using a custom cementless stem. Issue 5 (September 2019) - Dessyn, Edouard; Flecher, Xavier; Parratte, Sebastien; Ollivier, Matthieu; Argenson, Jean-Noël
Aim: The purpose of this study is to report the 20-year follow-up of a continuous series of 232 total hip arthroplasties (THAs) performed in patients aged less than 50 at the index surgery. Patients and methods: This is a retrospective monocentric study which reports the clinical, radiographical and survival results of 232 THAs performed with a custom cementless femoral stem in 212 patients evaluated at follow-up ranging from 14 to 27 years. Results: At the time of follow-up, the mean Harris Hip Score was 94.1 (range 48–100). The Hip disability and Osteoarthritis Outcome Score was >80 points in all 5 categories for 146 patients (68.9%). 18 hips (8.5%) showed radiographical femoral abnormalities. 23 hips (10.8%) underwent revision of the implants. 13 were isolated cup revisions. 3 more hips had bipolar revisions for aseptic loosening at 15, 20 and 21 years. Taking stem revision for aseptic loosening as an endpoint, survivorship was 96.8% at 20 years (95% confidence interval, 95.1–98.5; patients at risk 76) and 94.5% at 25 years (91.7–97.3; patients at risk 12). Conclusions: The results of this study confirm that THA using this custom-designed stem can provide excellent clinical and radiographical outcomes at a mean follow-up of 20 years in patients younger than 50. The individual 3D femoral stem and prosthetic neck has been able to restore extra- and intramedullary functional anatomy in this young and active cohort of patients.